Contentious migrant solidarity shrinking spaces and civil society contestation - Della Porta, Donatella 1956-; Steinhilper, Elias 1985- (Routledge, Taylor & Francis Group, 2022)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- List of figures -- List of tables -- Notes on the contributors -- 1 Shrinking spaces and civil society contestation: an introduction -- 2 (Un)Contentious solidarity at sea: the shifting politics of nongovernmental rescue activities in the Mediterranean -- 3 The criminalisation of solidarity: Asylum-seekers and Australia's illiberal-democracy -- 4 Crimmigration and solidarity in the global city: the case of Barcelona's street vendors -- 5 Keeping it private or making it political? "Soft repression" and the depoliticisation of everyday conversations among pro-refugee volunteers -- 6 Shrinking digital spaces: the hijacking of #refugees welcome campaigns on Twitter -- 7 Bureaucracy as border: barriers to social rights in Spain -- 8 Mountain patrols at the Franco-Italian border: performing solidarity, dissent and citizenship -- 9 Scale-switching as a response to a shrinking space for solidarity: a comparison of Denmark's Venligboerne and Germany's Seebrücke -- 10 Emotions in shrinking spaces for migrant solidarity: the protest campaign in the "Diciotti Ship Affair" at the Port of Catania -- 11 Counterprotest and anti-racist solidarity in the Trump era -- 12 The "solidarity crime" in the Maritime Alps: exploring the effects of criminal trials on migrant solidarity networks -- Index
Description based on publisher supplied metadata and other sources
Keywords: Soziales Engagement; Gruppenkohäsion; Migration; Zivilgesellschaft; Unterdrückung; Solidarität; Electronic books